Lessons learnt in CCAFS Flagship 4 Phase II - Born, Lorna (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This review of work conducted under Flagship Program 4 of CCAFS aims to document some of the challenges, opportunities and lessons learned in the past 5 years of research and implementation. Flagship 4 focuses on Climate Services and Safety Nets in Latin America, Asia and Africa, encompassing climate services design and implementation, insurance and early warning systems. An approach to quantifying lessons learned was developed, based on the climate services value chain and the institutions, assumptions and scaling strategies employed in the projects. Interviews with project leads offered insight into nuances and context-specific learning on implementing impactful projects. Results highlighted, amongst others, the importance of using varied metrics and strategies to measure impact; of considering timescales of the projects, from the macro-scale enabling environment to the granular decisions made by farmers; of actively working to understand the context of interventions; and of evaluating how climate information is used in decision-making.